З історії музейної справи в Центральній Україні у роки нацистської окупації (за матеріалами пропагандистської преси окупованих українських територій) - Грінченко, В.Г. (Сіверщина в історії України, 2020)
У статті висвітлюються окремі аспекти музейної справи
окупаційного періоду в Центральній Україні. Предметом розгляду є експозиційна робота музеїв та поповнення музейних зібрань
новими матеріалами.
З’ясовано, що музеї змушені були пристосовуватись до реалій «нового порядку», і це наклало відбиток на їхню експозиційну
діяльність. У найбільш одіозних проявах вона сприяла поширенню нацистської пропаганди, але ці прояви не були масовими. У
публікаціях, присвячених музеям, робився акцент на відродженні української культури під егідою окупаційної влади. Набували
пріоритетності релігійний і етнографічний напрями в експозиції музеїв. Брак експонатів після евакуаційних заходів радянської
влади змусив ряд музеїв звертатися до населення своїх регіонів
із проханням допомогти у вирішенні цього питання. Поповнення
музейних фондів новими цінними історичними матеріалами загалом мало епізодичний характер. The main purpose of the article is to highlight some aspects of the
museum affairs during the occupation period in Central Ukraine: on
the territory of modern Vinnytsia, Cherkasy, Kirovohrad, Poltava and
Dnipropetrovsk regions. The subject of investigation is the museums’
exhibit work, as well as the replenishment of museum collections with
new materials. In this context, the Dnipropetrovsk Historical Museum,
Vinnytsia, Poltava, Kremenchuh, Kirovohrad, Myrhorod, Cherkasy local
history museums, T. H. Shevchenko Memorial Museum in Kyrylivka,
M. М. Kotsiubynskyi Vinnytsia House-Museum have been mentioned
within the limits of the article.
It was found that, like other cultural-educational institutions, museums
were forced to adapt to the realities of the «New Order» in the conditions
of occupation, and this had left a mark on their activities, including the
exposition. It actually contributed to the spread of Nazi propaganda
in its most odious manifestations. However, the acquaintance with the
available newspaper material did not suggest that these manifestations
were widespread. In publications devoted to museums the emphasis was
focused on the revival of Ukrainian culture under the auspices of the
occupying power, which aimed to promote loyalty to the local population.
Religious and ethnographic trends in museum exhibitions had become
a priority and had a new meaning. The lack of necessary exhibits after
the Soviet authorities’evacuation measures forced the workers of several
museums to ask the people of their regions to help in solving this issue
for appropriate remuneration, and to make considerable efforts for their
independent production. The replenishment of museum funds with new
valuable historical materials was, on the whole, episodic. Along with this,
the testimonials about interesting and rather large-scale archeological
finds that have come to museums have been presented in the press.